Antiproliferative, antibacterial, and antioxidant activities of Bauhinia strychnifolia Craib aqueous extracts in gut and liver perspective - Suranat Phonghanpot; Faongchat Jarintanan (BMC, 2021)
Abstract Background Bauhinia strychnifolia Craib is an herb in Thai traditional medicine. Its decoction is traditionally used as an anticancer, antidiarrheal, and hangover remedy for centuries. Several studies described bioactivities of its organic solvent extracts, however, only few demonstrated the usefulness of the decoction. Here, we aimed to determine the bioactivities of Bauhinia strychnifolia Craib root and stem aqueous extracts in gut and liver perspective. Methods To achieve the goal, we performed MTT test, microscopic analyses, disc diffusion assay, broth microdilution assay, free radicals scavenging assays, and LC-MS analysis. Results We found that the extracts inhibited the growth of human hepatocellular carcinoma (HepG2) and colon adenocarcinoma (HT-29) cell lines. Moreover, they also inhibited the growth of gram-positive bacteria Staphylococcus aureus and Bacillus cereus but not inhibited the growth of gram-negative bacteria Escherichia coli and Pseudomonas aeruginosa. Furthermore, the extracts exhibited moderate antioxidant activity and increased GSH production in HepG2 cell line when compared with untreated. Our LC-MS analysis confirmed the existence of anticancer and antioxidant; 3,5,7,3',5'-pentahydroxyflavanonol-3-O-α-L-rhamnopyranoside and β-sitosterol, in the extracts. Conclusion The results from our study supported that the administration of Bauhinia strychnifolia Craib root and stem decoction would really aid colon or liver cancer patients and detoxify the alcoholic drunkard as it is claimed in Thai traditional medicine.